2004
DOI: 10.3201/eid1008.040047
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio vulnificusin Taiwan

Abstract: Clinical features of 84 patients with V. vulnificus infection are analyzed and molecular features of isolates are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 24 publications
7
90
2
Order By: Relevance
“…They recommended using molecular typing to study the epidemiology of V. vulnificus infections (Sanjuán & Amaro 2007, Sanjuán et al 2009). Although biotype 1 was considered to be primarily pathogenic to humans and mainly foodborne (Tison et al 1982, Hsueh et al 2004, based on our results of hiMLST, we found no identical published human strains in the database (http://pubmlst.org/ vvulnificus). However, the isolated zoonotic biotype 2 strain ST 112 correlated perfectly to the ST 112 of the database.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…They recommended using molecular typing to study the epidemiology of V. vulnificus infections (Sanjuán & Amaro 2007, Sanjuán et al 2009). Although biotype 1 was considered to be primarily pathogenic to humans and mainly foodborne (Tison et al 1982, Hsueh et al 2004, based on our results of hiMLST, we found no identical published human strains in the database (http://pubmlst.org/ vvulnificus). However, the isolated zoonotic biotype 2 strain ST 112 correlated perfectly to the ST 112 of the database.…”
Section: Discussionmentioning
confidence: 79%
“…water, eels) and clinical isolates (Tison et al 1982, Tsai et al 1990). Biotype 1 has been isolated from seawater (Veenstra et al 1993a,b, Hor et al 1995, Hsueh et al 2004), eels and oysters (Coleman et al 1996) but has thus far been considered non-pathogenic for eels , Coleman et al 1996, although it can cause disease in tilapia and carp (Sakata & Hattori 1988). Biotype 2 has mainly been found in diseased eels (Tsai et al 1990, Biosca et al 1991.…”
Section: Introductionmentioning
confidence: 99%
“…Among healthy persons, V. vulnificus infection is most likely associated with a history of cutaneous injury caused by handling seafood, which can allow the bacteria to enter the body through an open wound. The risk of exposure is more important in this locality than in other areas where swimming or eating raw oysters and undercooked seafood are the major risk factors (4,(6)(7)(8), possibly because fresh seafood is widely consumed, and seafood is easily accessible in wet markets in Hong Kong. Our study shows that the risk is higher during the summer, which is consistent with the fact that V. vulnificus is more active in warmer temperatures (9).…”
Section: Cutaneous Injury and Vibrio Vulnificus Infectionmentioning
confidence: 99%
“…For example, aggregation and particle settling presents an efficient mode of bacterial removal from surface waters (e.g., Characklis et al 2005), potentially altering the exposure of local populations using the affected water body (e.g., Maugeri et al 2004). In addition, attachment to phytoplankton cells may affect the concentrations accumulated in shellfish, which is a major route of exposure to Vibrio (Murphree and Tamplin 1995, Linkous and Oliver 1999, Hsueh et al 2004, Marino et al 2005.…”
Section: Introductionmentioning
confidence: 99%